1989
DOI: 10.1007/bf02185857
|View full text |Cite
|
Sign up to set email alerts
|

Importance of blood volume cultured in the detection of bacteremia

Abstract: The influence of the volume of blood cultured on the rate of detection of bacteremia was evaluated in a routine 12-tube blood culture system using 1693 samples from 1502 patients. Blood samples were drawn simultaneously into two transport tubes. The blood volume cultured was the only varying parameter. Generally, 17% more cultures with clinically significant microorganisms (both Enterobacteriaceae and gram-positive cocci) were found when blood from two instead of one tube was used (in most cases comparing 13-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 18 publications
2
53
0
Order By: Relevance
“…Numerous factors influence the likelihood of detecting bacteremia. These factors include the volume of blood specimens cultured and the number of blood cultures performed (1,8,10,11,17,21,25,27,29). The conventional practice has been to obtain blood specimens at or around the time of a temperature elevation as a means of enhancing the likelihood of documenting bacteremia (5,32).…”
mentioning
confidence: 99%
“…Numerous factors influence the likelihood of detecting bacteremia. These factors include the volume of blood specimens cultured and the number of blood cultures performed (1,8,10,11,17,21,25,27,29). The conventional practice has been to obtain blood specimens at or around the time of a temperature elevation as a means of enhancing the likelihood of documenting bacteremia (5,32).…”
mentioning
confidence: 99%
“…One of the most important factors influencing blood culture diagnostic yield is blood volume (71,191). Several studies of adults (4,17,30,84,126) and pediatric patients (82,86) confirmed that the rate of isolation from blood cultures increases with the quantity of blood submitted. This is particularly important for pediatric patients, for whom it is not always possible to draw a sufficient volume of blood.…”
Section: The Limits Of a Gold Standard: Factors Influencing Blood Culmentioning
confidence: 90%
“…The reported detection limit for SeptiFast real-time PCR is 3-100 CFU/ml 29 which compares relatively favourably to the microbial burden often associated with adult sepsis (< 10 CFU/ml). 23,97 However, this varies considerably between species with some organisms including C. glabrata, being undetectable at 3 CFU/ml blood. A similar explanation could be proposed for the performance of the test in detecting CoNS.…”
Section: Discussionmentioning
confidence: 99%
“…The amplification of the pathogen signal during real-time PCR is crucially important owing to the low numbers of circulating bacteria [10 colony-forming units (CFUs) per ml] or fungi (1-10 CFU/ml) reported in adult sepsis. 23,24 The use of real-time PCR also facilitates detection of fastidious, difficult-to-culture organisms such as fungi. 25 Two basic approaches have been taken in the design of real-time PCR assays for sepsis pathogens, either (i) broad-range detection of bacterial or fungal DNA with universal primers followed by species identification using post-PCR techniques such as DNA sequencing, electrospray ionisation mass-spectrometry or high resolution melting analysis [26][27][28] or (ii) multiplex assays utilising a panel of species-specific hybridisation probes that provide direct confirmation that a particular species is present.…”
Section: Molecular Approaches To Diagnosis Of Health-care-associated mentioning
confidence: 99%